Design of Production System Improvement to Increase Productivity with Quality Control Circle Approach: Perancangan Perbaikan Sistem Produksi Untuk Peningkatan Produktivitas Dengan Pendekatan Quality Control Circle - Rabbani, Muhammad Rayhan; Mansur, Agus (Universitas Muhammadiyah Sidoarjo, 2024)
The increase in population has an impact on increasing community needs, especially in Indonesian sugar commodities. PG XYZ is one of the sugar production companies in Indonesia that targets a milling capacity of 5,750 tth. PG XYZ faced high sugar reject, so it needed to be reprocessed which had an impact hampering factory productivity. Data from the 2022 milling season shows that rejected sugar is at 5.15% with a total loss of IDR 1,619,300 for each ton. Therefore, it’s necessary to minimize the occurrence of rejected sugar. This research focuses on increasing quality productivity using a series of Quality Control Groups with PDCA stages on manufacturing parts. Data were collected through a FMEA questionnaire. The results showed the obstacles were pol blotong > 2.5%, outputting A < 55%, HK drops > 32%, and sugar reject due to black spots > 1%. The improvement plan is carried out by separating and creating a new clean water line for the supply of vacuum pump coolant, procurement, and installation of stirrer pans. The implementation was carried out for D1/D2 vacuum pan which showed a decrease in reject sugar due to black spots by 182.90 tons or 0.13% with a total of Rp 296,164,764.